2018
DOI: 10.1002/uog.19092
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of fetuses with congenital parvovirus B19 infection: systematic review and meta‐analysis

Abstract: Hydrops is the main determinant of mortality and adverse perinatal outcome in fetuses with PB19 infection. Perinatal outcome in non-hydropic fetuses is generally favorable. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 51 publications
0
54
0
2
Order By: Relevance
“…Moreover, mature erythrocytes are transfused, which are less susceptible to the influence of parvovirus, and therefore likely to persist for the normal erythrocyte half-life of 120 days. A meta-analysis of observational studies showed that intrauterine blood transfusion resulted in resolution of hydrops in 55% of affected fetuses, whereas resolution of anemia on follow-up scans was reported in all non-hydropic fetuses 140 . Finally, transfused blood, if taken from a donor seropositive for parvovirus IgG, can confer some passive immunity on the fetus.…”
Section: Management Of Maternal and Fetal Parvovirus B19 Infectionmentioning
confidence: 99%
“…Moreover, mature erythrocytes are transfused, which are less susceptible to the influence of parvovirus, and therefore likely to persist for the normal erythrocyte half-life of 120 days. A meta-analysis of observational studies showed that intrauterine blood transfusion resulted in resolution of hydrops in 55% of affected fetuses, whereas resolution of anemia on follow-up scans was reported in all non-hydropic fetuses 140 . Finally, transfused blood, if taken from a donor seropositive for parvovirus IgG, can confer some passive immunity on the fetus.…”
Section: Management Of Maternal and Fetal Parvovirus B19 Infectionmentioning
confidence: 99%
“…Fetal hydrops, or abnormal accumulation of fluid/edema in two or more compartments, is common in the setting of Parvovirus B19 infection, with a metaanalysis finding a 9.3% pooled incidence, as well as an increased risk of fetal loss, spontaneous abortion and stillbirth [36]. Parvovirus B19 is among the most common causes of non-immune fetal hydrops, and while spontaneous resolution of infection can occur, only about 5% of cases with hydrops will show spontaneous resolution of the infection with disappearance of hydrops on follow up ultrasounds [37].…”
Section: Parvovirus B19mentioning
confidence: 99%
“…In utero transfusions (IUT) are often necessary and reduce mortality rates when compared to expectant management. A metaanalysis found IUT was performed in 78% of hydropic fetuses compared to 29% of non-hydropic fetuses, with the difference likely due to the hydropic fetuses at higher risk of demise [37]. Complications may occur in up to 5% of cases, especially if the fetus is likely more sensitive to vascular overload [38].…”
Section: Parvovirus B19mentioning
confidence: 99%
“…For sophisticated epidemiological models and related data, see [13][14][15]. The virus can be transmitted from mother to fetus posing a risk of fetal damage that should prompt for an antenatal assessment of risk of fetal infections and diagnostic attention towards the development of intrauterine infections (see [16][17][18] for recent reviews). Finally, due to a viremic phase with high viral load, there is a risk of iatrogenic transmission of the virus via blood and blood-derived products, implying blood and blood product safety issues (see [19,20] for recent reviews).…”
Section: Transmissionmentioning
confidence: 99%
“…Hydrops may eventually cause fetal death, but frequently the fetus can recover without persistent developmental damage. In the third trimester the overall risk of fetal damage decreases to background values, although late intrauterine fetal death can occur [17,59]. Conservative management of documented infections is advised, with an indication for improved survival following intrauterine transfusions in case of documented fetal anemia below a threshold level [60].…”
Section: Fetal Infectionmentioning
confidence: 99%